GYNECOLOGICAL TUMORS AND MALIGNANT CONDITIONS: PATHOPHYSIOLOGY, DIAGNOSIS, AND TREATMENT (Web of Teachers: Inderscience Research, 2025)
Gynecological cancers, including those of the uterus, ovaries, cervix, vulva, and vagina, represent a significant cause of morbidity and mortality in women worldwide. These malignancies are characterized by complex pathophysiological mechanisms that involve genetic mutations, hormonal imbalances, environmental factors, and immune dysfunction. Early diagnosis and intervention are crucial for improving survival rates, but challenges in detecting gynecological cancers at an early stage persist. This paper reviews the major types of gynecological malignancies, focusing on their pathophysiology, risk factors, molecular pathways, and current approaches to diagnosis and treatment. We also discuss the impact of emerging therapies and personalized medicine in the management of these cancers.